Incorporación al Régimen de la Seguridad Social Ecuatoriana a los Operarios y Aprendices que Laboran bajo Dependencia de los Artesanos y el Derecho de las Prestaciones Sociales - Pinzon Chuquirima, Lorena Viviana (2017)
This research paper entitled: "Incorporation To The Scheme Of Social Security Of Ecuador To Operators And Apprentices Who Work Under Dependency" we have done in based on the study and analysis of legal institutions and the legal basis governing rights workers and the general rights to benefits under the compulsory general insurance that was our problem and research topic. We also studied the doctrine of different writers to acquire knowledge and provide clearer researcher with his personal analysis to reach the objectives. The purpose of this research we make an article where it is artisanal workers include all social benefits and eliminate discrimination that they have been taking is punishable. The rights and guarantees that the Constitution gives all individuals are inalienable therefore should be given compliments to them in case of failure to do so should punish these people because they are violating important rights, the Labour Code excludes the workers of social benefits because they have been left unprotected and violating the Constitutional rights. In the main thing we want to achieve is justice workers and apprentices operators who work under the regime of dependence according to the principles governing the Constitution of the Republic of Ecuador.